The Influence of Conflict Management and Professional Ethics on Teacher Job Satisfaction at Muhammadiyah Schools in Bangkinang - Taufik, Irfan; Sumarno, Sumarno; Bunari, Bunari (Journal Corner of Education, Linguistics, and Literature, 2024)
This study aims to analyze the influence of conflict management and professional ethics on teacher job satisfaction at Muhammadiyah Schools in Bangkinang. The research is motivated by the importance of fostering a harmonious and professional work environment to enhance teacher performance and commitment. A quantitative approach was employed, utilizing a survey method and multiple linear regression analysis. The findings reveal that both conflict management and professional ethics have a significant and positive impact on job satisfaction. The coefficient of determination (R²) value of 0.569 indicates that 56.9% of the variation in job satisfaction is explained by these two variables. Both independently and jointly, they contribute substantially to building a productive and supportive teaching environment. These results affirm that effective conflict management strategies and the consistent application of professional ethics are critical factors in fostering job satisfaction. The integration of these elements enhances morale, reduces potential conflict, and strengthens relationships among educators, ultimately improving the quality of education.